USULAN PENERAPAN MANAJEMEN RESIKO KECELAKAAN KERJA DENGAN METODE MULTI ATTRIBUTE FAILURE MODE ANALYSIS (MAFMA) (Studi Kasus : PT. Semen Gresik Tbk Pabrik Rembang) - Irwan Sukendar; Akhmad Syakhroni; Maristya Senja (Jurnal Ilmiah Dinamika Teknik, 2021)
Semen Gresik Tbk is one of a company engaged in manufacturing which produces cement located in Rembang regency. In the production process, there is a potential related to the risk of work accidents from minor accident to serious accident. This is an obstacle to smooth running of the production process. In term of the company experiencing losses due to human casualities, property and hampering productivity due to the number of lost work days. With the problem experienced, it requires a structured identification, measurement and handling of risks to reduce losses from risks. One method relation to the risk manajement is Multi Attribute Failure Mode Analysis (MAFMA) as an effort to reduce losses due to critical risks that could potentially occur in the cemment production process. The MAFMA method is the development of the Failure Mode and Effect Analysis (FMEA) method which is used to determine the causes of potential failures by adding economic or cost factors to the risk assessment using the AHP (Analytic Hierarchy Process) method. From the research that has been done, it is obtained that the highest risk is the risk of falling from a height with a total risk of 0,108 and the risk of being electrocuted with a total risk of 0,091.